Rancang Bangun Sistem Informasi Geografis Pemetaan Sekolah di Kecamatan Entikong Berbasis Website Menggunakan Laravel, React.Js, Mapbox dan Progressive Web Apps - Ade Muhammad Thoha; Aditya Pratama; Awanis Hidayati (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to produce a geographic information system based on a school mapping website in Entikong District. A total of 12 Elementary Schools (SD), 5 Junior High Schools (SMP), 1 Madrasah Tsanawiyah School (MTS) and 2 Vocational High Schools (SMK) were the subjects of this study. The process of creating a geographic information system goes through several stages, including system planning using flowcharts and unified modeling language (UML), at the design stage, the system is designed in a wireframe using mockflow tools wireframing, to creating a geographic information system using laravel, react. js, mapbox and progressive web apss. Then the system is tested using blackbox testing. This system makes it easy for users to find out the location of schools in Entikong District which is supported by the open direction feature. Based on this research, it allows users to search and find relevant information for each school in Entikong District.